(untitled) (Journal of Informatics and Mathematical Sciences, 2016)
Let \(X\) denote a set of non-negative integers and \(P(X)\) be its power set. An integer additive set-labeling (IASL) of a graph \(G\) is an injective set-valued function \(f:V(G)→ P(X)-{}\) where induced function \(f^+:E(G) → P(X)-{}\) is defined by \(f^+ (uv) = f(u)+ f(v)\), where \(f(u)+f(v)\) is the sumset of \(f(u)\) and \(f(v)\). Let \(f(x)=mx+c\); \(mN\), \(cN_0\). A finite linear Jaco graph, denoted by \(J_n(f(x))\), is a directed graph with vertex set \({v_i: iN}\) such that \((v_i,v_j)\) is an arc of \(J_n(f(x))\) if and only if \(f(i)+i-d^-(v_j)j\). In this paper, we discuss the admissibility of different types of integer additive set-labeling by finite linear Jaco graphs.